Recurrent leiomyoma of the vulva mimicking peripheral nerve sheath tumour. Issue 12 (8th December 2019) - Kothandaraman, Keerthana; Dorairajan, Gowri; Subbaiah, Murali; Dorairajan, LN; Badhe, Bhawana A; Keepanasseril, Anish
Abstract : Leiomyoma, a benign monoclonal tumour, is very rarely found in extrauterine sites, especially in the vulval region. Histopathology of the soft tissue tumours affecting this region is similar and immunohistochemistry (IHC) may be essential to confirm the diagnosis. We report a case of a 63-year-old postmenopausal woman who presented with a recurrent vulval mass involving the clitoris and left labia majora with suspected urethral involvement. Although the wedge biopsy was reported as peripheral nerve sheath tumour, staining with smooth muscle actin clinched the diagnosis of leiomyoma, highlighting the importance of IHC for diagnosis.